The occupation of Pretoria on 5th June, 1900 (Historia, 2021)
The  Republican   ultimatum   to   Great  Britain,   delivered   on  October  9,1899, had  resulted  in  the  war  breaking   out  on  October  11,  and  martial   lawwas  proclaimed    in  the  two  Republics.   The   initial    Republican   victories   inNatal  had  been succeeded by  retreats  not  only  there  but  on  all  other  fronts.Ladysmith   and  Mafeking   were   reliewd,    Bloemfontein,   the   capital   of   thesister  Republic,  was occupied  on  March  13,  1900,  and  now  Frederick  Sleigh,Baron  Roberts   of   Kandahar   and   Waterford,    Commander-in-Chief    of   HerMajesty's Forces in  South Mrica,  was marching  from  the  Free  State toPretoria   with  his  forces  at  an  average rate  of  nearly   17 miles  per  marchingday  -a performance   almost  equal  to  the  best recorded  in  military    historyup  to  then  -with the  commanders  on  the  other  fronts  trying   to  keep  pacewith  him.Although    Lord   Roberts's   advance  was  delayed   by   actions   here  andthere, the  Vaal  River  was  crossed somewhere near  Viljoensdrift    without   anyserious  opposition,  and  the  British   Army  found  itself   within  striking   distanceof  the  Rand  gold  mines  -one of  the  main  causes of  the  war.By  this   time,   General  Louis   Botha,  unknown   soldier   at  the  outbreakof  war,  had  succeeded General  Piet  Joubert  and  was,  at  this   stage, actingCommandant-General  of  the  Transvaal  forces.Mainly   due  to  his  strong  stand  -and, let  it  not  be  forgotten,   that  ofPresident  Kruger  -the British  found  the  gold  mines  undamaged  when  theyentered  Johannesburg   on  May  31.    The  Republican   Government,  in  spiteof  strong  demands  and  even  personal  attempts  by  some  members  to  blowup  the  mines,  had  not  been  able  to  agree to  any  "scorched  earth"   policy.Meanwhile,  the  Volksraad   on  May  7,  met  for  the  last  time  in  Pretoria.It  was  a  sad  occasion  for   the  members  -with many  empty  seats  in  theVolksraad   Chamber draped  in  crepe, previously  occupied  by  prominent  mem-bers  who  by  then  had  made  the  supreme  sacrifice.    Another   empty  seat wasthat of  General Botha  who  was away  at the front.
Keywords: Occupation; Paul Kruger; Pretoria; Rand gold mines; General Louis Botha